Measuring the Attribute Accuracy and Completeness for the OpenStreetMap Roads Networks for Two Regions in Iraq (Journal of Engineering, 2023)
The OpenStreetMap (OSM) project aims to establish a free geospatial database for the entire world which is editable by international volunteers. The OSM database contains a wide range of different types of geographical data and characteristics, including highways, buildings, and land use regions. The varying scientific backgrounds of the volunteers can affect the quality of the spatial data that is produced and shared on the internet as an OSM dataset. This study aims to compare the completeness and attribute accuracy of the OSM road networks with the data supplied by a digitizing process for areas in the Baghdad and Thi-Qar governorates. The analyses are primarily based on calculating the portion of the commission (extra road) and omission (missing road) for OSM roads. The calculations also involved measuring the classifications and the attribute correctness associated with geometrical shapes. The results indicated that the completion rates were very high in the two study areas, and the percentages of labels or names were low in the two study areas. However, it was better on the main roads than in other road classes.